2015
DOI: 10.17221/7/2015-pse
|View full text |Cite
|
Sign up to set email alerts
|

Application of fluorescence spectrum to precisely inverse paddy rice nitrogen content

Abstract: Paddy rice is important for Chinese agriculture and crop production, which largely depends on the leaf nitrogen (N) levels. The purpose of this study is to discuss the relationship between the fluorescence parameters and leaf N content of paddy rice and to test their performance in inversing N content of crops through back-propagation (B-P) neural network. In the correlative analysis of the fluorescence parameters and the N content, we found that the correlation between fluorescence ratios (F740/F685 and F685/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
17
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 18 publications
1
17
0
Order By: Relevance
“…Fluorescence ratios (F 740 /F 685 and F 685 /F 525 ) were widely utilized for the estimation of the nitrogen status and for the diagnosis of crop growth because of their simplicity in measurement and interpretation [11,46]. However, studies of Yang Jian et al [47] indicated that these fluorescence ratios were insensitive to the rice LNC. On the contrary, the rice LNC was closely correlated with the intensity of the fluorescence peaks (F 450 , F 685 and F 740 ).…”
Section: Lnc Estimation Using Reflectance Spectrum and Reflectance + mentioning
confidence: 99%
“…Fluorescence ratios (F 740 /F 685 and F 685 /F 525 ) were widely utilized for the estimation of the nitrogen status and for the diagnosis of crop growth because of their simplicity in measurement and interpretation [11,46]. However, studies of Yang Jian et al [47] indicated that these fluorescence ratios were insensitive to the rice LNC. On the contrary, the rice LNC was closely correlated with the intensity of the fluorescence peaks (F 450 , F 685 and F 740 ).…”
Section: Lnc Estimation Using Reflectance Spectrum and Reflectance + mentioning
confidence: 99%
“…Related studies showed that the characteristic peaks of LIF spectra were closely related to the nutrient stress of crops (Tuba et al 2010, Yang et al 2015a). Due to the advantages of rapid, non-destruction and without pre-processing analysis, it has been widely used to estimate canopy N status of maize, tomato, wheat and paddy rice , Yang et al 2015b, Živčák et al 2014a). However, they mainly focused on using the far-red and red fluorescence ratios, fluorescence intensity as well as non-photochemical quenching etc.…”
mentioning
confidence: 99%
“…The reason is that its N content was lower than other treatments (Figure 1). In addition, compared with F735/F685, the fluorescence ratio of F735/F460 and F685/ F460 both exhibited significant differences among different N fertilization levels in and 2015. McMurtrey et al (1994 and Subhash and Mohanan (1994) achieved the same variation tendency of fluorescence characteristics for different dose of N fertilization.…”
mentioning
confidence: 87%
“…In subsequent investigations, LIF technology was utilized to monitor the environment's (e.g., light stress, high temperature and drought (Živčák et al 2008) influence on soybean, wheat and rice. In addition, Yang et al (2015) analysed the correlation between fluorescence peaks and leaf N content in paddy rice. Thus, LIF is a helpful method in monitoring of the nutrient stress of plants.…”
mentioning
confidence: 99%